2007
DOI: 10.1007/s11239-007-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct-to-patient expert system and home INR monitoring improves control of oral anticoagulation

Abstract: This novel approach of internet-supervised patient self-management improved time in therapeutic range compared to an anticoagulation clinic. This is the first demonstration of an internet-based expert system enabling remote and effective management of patients on oral anticoagulants. Expert systems may be applicable for management of other chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
3
28
0
1
Order By: Relevance
“…Our results are consistent with the improvements in TTR associated with PST and online systems in three other studies [17,37,38]. The studies by O’Shea et al [17] and Ryan et al [37] used the same Internet-based system, which provided a decision-support tool to assist patients adjust their own warfarin dose.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are consistent with the improvements in TTR associated with PST and online systems in three other studies [17,37,38]. The studies by O’Shea et al [17] and Ryan et al [37] used the same Internet-based system, which provided a decision-support tool to assist patients adjust their own warfarin dose.…”
Section: Discussionsupporting
confidence: 90%
“…The literature suggests that patients in the community spend 50-60% of their time within the target range [16]. It was envisaged that this could be improved to 75% with the intervention based on a prior study involving a similar intervention [17]. At a power of 80% and statistical significance set at 0.05, 16 patients analyzed before and after were required.…”
Section: Methodsmentioning
confidence: 99%
“…If good anticoagulation control cannot be achieved within the usual care setting, specialized anticoagulation management such as anticoagulation clinics or handheld patient INR meters are validated alternative options [5,25]. Finally, substitution with newer oral anticoagulants is inevitable in patients with NVAF.…”
Section: Discussionmentioning
confidence: 99%
“…For those undertaking self-testing, specific details of the arrangements for adjustment of dosage were not captured. Several studies have however shown improvements in therapeutic control in patients that self-test and have direct access to an internet-based decision support system or clinical supervisor for dosing advice 19 21 22. In a prospective, single-group, before and after study, O’ Shea et al demonstrated an increase in therapeutic time in range from 63% in the anticoagulation clinic to 74% during internet supervision 21.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have however shown improvements in therapeutic control in patients that self-test and have direct access to an internet-based decision support system or clinical supervisor for dosing advice 19 21 22. In a prospective, single-group, before and after study, O’ Shea et al demonstrated an increase in therapeutic time in range from 63% in the anticoagulation clinic to 74% during internet supervision 21. Similarly, a subsequent randomised, cross-over study, using the same internet-based system, reported an improvement in therapeutic control from 59% to 74% 19.…”
Section: Discussionmentioning
confidence: 99%